The influence of climate and population structure on East Asian skeletal morphology. Issue 173 (December 2022) - Cho, Elizabeth O.; Cowgill, Libby W.; Middleton, Kevin M.; Blomquist, Gregory E.; Savoldi, Fabio; Tsoi, James; Bornstein, Michael M.
Abstract: Recent studies have shown that global variation in body proportions is more complex than previously thought as some traits formerly associated with climate adaptation are better explained by geographic proximity and neutral evolutionary forces. While the recent incorporation of quantitative genetic methodologies has improved understanding of patterns related to climate in Africa, Europe, and the Americas, Asia remains underrepresented in recent and historic studies of body form. As ecogeographic studies tend to focus on male morphology, potential sex differences in features influenced by climate remain largely unexplored. Skeletal measurements encompassing the dimensions of the skull, pelvis, limbs, hands, and feet were collected from male ( n = 459) and female ( n = 442) remains curated in 13 collections across seven countries in East Asia ( n = 901). Osteological data were analyzed with sex and minimum temperature as covariates adjusted by autosomal single-nucleotide polymorphism population genetic distance using univariate Bayesian linear mixed models, and credible intervals were calculated for each trait. Analysis supports a relationship between specific traits and climate as well as providing the magnitude of response in both sexes. After accounting for genetic distance between populations, greater association between climate and morphology was found in postcranial traits, with the relationship between climate and the skull limited primarily to breadth measurements. Larger body size is associated with colder climates with most measurements increasing with decreased temperature. The same traits were not always associated with climate for males and females nor correlated with the same intensity for both sexes. The varied directional association with climate for different regions of the skeleton and between the sexes underscores the necessity of future ecogeographic research to holistically evaluate body form and to look for sex-specific patterns to better understand population responses to environmental stresses. Highlights: Postcranial variation was found to more strongly associate with changes in climate. Body and limb size increased at higher latitudes and decreased at lower latitudes. Males and females did not always adapt to climate in the same manner or intensity. Nasal morphological variation was better explained by genetic relatedness.